If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 7)(9x + 7) = 0 Reorder the terms: (7 + 9x)(9x + 7) = 0 Reorder the terms: (7 + 9x)(7 + 9x) = 0 Multiply (7 + 9x) * (7 + 9x) (7(7 + 9x) + 9x * (7 + 9x)) = 0 ((7 * 7 + 9x * 7) + 9x * (7 + 9x)) = 0 ((49 + 63x) + 9x * (7 + 9x)) = 0 (49 + 63x + (7 * 9x + 9x * 9x)) = 0 (49 + 63x + (63x + 81x2)) = 0 Combine like terms: 63x + 63x = 126x (49 + 126x + 81x2) = 0 Solving 49 + 126x + 81x2 = 0 Solving for variable 'x'. Factor a trinomial. (7 + 9x)(7 + 9x) = 0Subproblem 1
Set the factor '(7 + 9x)' equal to zero and attempt to solve: Simplifying 7 + 9x = 0 Solving 7 + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = 0 + -7 9x = 0 + -7 Combine like terms: 0 + -7 = -7 9x = -7 Divide each side by '9'. x = -0.7777777778 Simplifying x = -0.7777777778Subproblem 2
Set the factor '(7 + 9x)' equal to zero and attempt to solve: Simplifying 7 + 9x = 0 Solving 7 + 9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = 0 + -7 9x = 0 + -7 Combine like terms: 0 + -7 = -7 9x = -7 Divide each side by '9'. x = -0.7777777778 Simplifying x = -0.7777777778Solution
x = {-0.7777777778, -0.7777777778}
| -16t^2+12t+4=0 | | 2(7x-2)(4x+3)=0 | | 4x^2+31x-17=0 | | -3+15v=-63 | | 4x^2+31x-19=2 | | 0=500n-2000 | | 16xy+28x+12y+21= | | -9r^3(7r^2+6)(7r^2-6)=0 | | 32w+8= | | x^2=-4x-20 | | -14x-14=2x+7 | | 4x^2+20x+19=6 | | 4y^4(2y+1)(y-6)=0 | | 3v^2+20+32=0 | | x^2+5=42 | | (3a-3d)(3a+2d)=0 | | 9+x=-125 | | 7x-28-30=33 | | 49x^2-3=06 | | 3+x=-150 | | 39x^2=36 | | 5+x=230 | | (3z-u)(3z+2u)=0 | | 4(X-20)=2X+10 | | .25p+.2(10-p)=0 | | (6-u)(4+2u)=0 | | 2+x=-34 | | -93=-3+-15x | | (9x+2)(9x+2)=0 | | 0.2(1.5z-5)=4(4z+1) | | x(445-4x)=10000 | | 10n-0.375=.1n-.375 |